2018
DOI: 10.1007/s11187-018-0038-0
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-five years of research on institutions, entrepreneurship, and economic growth: what has been learned?

Abstract: This paper analyzes an emergent stream of research shedding light on the institutional factors shaping entrepreneurial activity and its effect on economic growth. This integrative analysis spanning a broad spectrum of diverse literature enables a distinction between two different research lines in the field of entrepreneurship. The findings of this study, based on articles from the journals included in the Web of Science database, facilitate a broader comprehension of two separate lines of research, which allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
409
0
15

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 488 publications
(435 citation statements)
references
References 272 publications
(212 reference statements)
11
409
0
15
Order By: Relevance
“…culture) (Bruton et al, 2010). In this regard, it has been proven that institutional economics is a solid foundation for understanding the dynamics of entrepreneurial activity (Bruton et al, 2010;Thornton et al, 2011;Urbano et al, 2018; among others).…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…culture) (Bruton et al, 2010). In this regard, it has been proven that institutional economics is a solid foundation for understanding the dynamics of entrepreneurial activity (Bruton et al, 2010;Thornton et al, 2011;Urbano et al, 2018; among others).…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…Particularly, Urbano et al (2018) found, through a literature review, that informal institutions, though less explored, may exert a stronger influence on entrepreneurial activity than formal institutions. Among the informal factors, these authors suggested that cognitive aspects, such as leadership, can be a worthy element for future research.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…There have been many contributions to the literature on entrepreneurship and economic growth in recent years (see e.g., Urbano, Aparicio, & Audretsch, (2018) for a recent review).…”
Section: Models and Literature Developmentmentioning
confidence: 99%
“…Pro-market institutions can encourage a protection of property rights, which are important for capital accumulation and entrepreneurial investment (De Soto, 2000), but they can also reduce the adverse effects of regulation on entrepreneurial entry (Djankov et al, 2002;Ho & Wong, 2007;Klapper et al, 2006;Van Stel et al, 2007). Recent contributions have modeled this mechanism using a multi-stage analysis where institutions affect entrepreneurship in the first stage, which subsequently affects economic growth in the second stage (Bosma et al, 2018;Urbano et al, 2018). One conceptual way to model this relationship is through the Coleman bathtub model (Bjørnskov & Foss, 2016;Bradley & Klein, 2016;Kim et al, 2016), which is illustrated in Figure 1.…”
Section: The Nexus Of Institutions Entrepreneurship and Growthmentioning
confidence: 99%
“…This is associated with the special part for EA to play within the economic system (Noseleit, 2013;Mueller & Thomas, 2001). It is EA that is one of the fundamental factors ensuring achievement of the economic growth of both the country and its regions, the development of innovation potential and improvement of the population's quality of life (Bjørnskov& Foss, 2016; Sobel, 2008;Draskovicet al, 2017;Urbano et al, 2018). However, in the conditions of the Russian economy, entrepreneurial activity is characterized by unevenness both in terms of structural and regional distribution.…”
Section: Introductionmentioning
confidence: 99%